PENGARUH UKURAN PERUSAHAAN, FINANCIAL LEVERAGE, DIVIDEND PAYOUT RATIO, DAN NILAI PERUSAHAAN TERHADAP PERATAAN LABA - Yolanda Sesilia; A. Zubaidi Indra; Chara Pratami Tidespania Tubarad (Jurnal Akuntansi dan Keuangan (JAK), 2021)
This study aimed to examine the effect of Firm Size, Financial Leverage, Dividend Payout Ratio, and Firm Value toward Income Smoothing in BUMN Companies Listed on Indonesia Stock Exchange. Income Smoothing measured by Index Eckel’s. The Population in this study is BUMN companies listed on the Indonesia Stock Exchange in 2015-2019 Based on the purposive sampling method, the sum of a sample obtained from the population is 16 companies. Sources of data obtained from annual reports of companies listed on Indonesia Stock Exchange in 2015-2019. The analytical method for this study uses logistic regression analysis and Mann Whitney test with SPSS 21. Based on the result of the analysis showed Firm Size, Financial Leverage, Dividend Payout Ratio, and Firm Value are not influence Income Smoothing.